2010
DOI: 10.1016/j.jaut.2009.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and rheumatoid arthritis: The role of SENP1 in the regulation of MMP-1 expression

Abstract: The aggressive phenotype of RA synovial fibroblasts (RASF) is characterised by the increased expression of matrix metalloproteinase (MMP)-1 as well as the small ubiquitin like modifier (SUMO)-1 and decreased expression of SUMO-specific protease SENP1. Since we showed an increased activity of acetyltransferases in this autoimmune disease, we wanted to analyse whether this affects the expression of MMP-1 and can be reversed by the reconstitution of SENP1.In RASF, the acetylation of histone H4 was significantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
41
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 32 publications
(36 reference statements)
6
41
0
2
Order By: Relevance
“…Consistent with our results, a previous study showed that PAK1, a downstream effector of PIAS3 that has been demonstrated in the present work, also regulated MMP-13 expression in RA FLSs (44). SENP1, which served as a deSUMOylation enzyme, participated in the regulation of MMP-1 expression in RA FLSs (45). These results therefore suggest that one of the mechanisms of PIAS3 involved in pathogenesis of RA is regulating MMPs production.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our results, a previous study showed that PAK1, a downstream effector of PIAS3 that has been demonstrated in the present work, also regulated MMP-13 expression in RA FLSs (44). SENP1, which served as a deSUMOylation enzyme, participated in the regulation of MMP-1 expression in RA FLSs (45). These results therefore suggest that one of the mechanisms of PIAS3 involved in pathogenesis of RA is regulating MMPs production.…”
Section: Discussionsupporting
confidence: 93%
“…It has been established that the proMMP-1 gene expression requires chromatin remodeling in part via histone posttranslational modifications (18)(19)(20)(21)(22). A previous study showed that proMMP-1 gene expression induced by TPA in T98G cells involved a dynamic and ordered recruitment of enzymes allowing H3/H4 acetylation, H3K4 di-and trimethylation, H3S10 phosphorylation and chromatin opening (22).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, only a few reports have addressed how methylation of individual CpG sites influences the promoter activity of a specific gene (6,10,11), and the relative contributions of the methylation status of each individual CpG site to the transcriptional regulation of a given gene in vivo remain largely unexplored. In addition, although epigenetic gene regulation has been broadly investigated in other contexts, little is known about the specific impact of this mechanism of gene control in musculoskeletal diseases (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%